Cortical Gating of Oropharyngeal Sensory Stimuli - Wheeler-Hegland, Karen; Pitts, Teresa; Davenport, Paul W. (Frontiers in Physiology, 2011)
Somatosensory evoked potentials provide a measure of cortical neuronal activation in response to various types of sensory stimuli. In order to prevent flooding of the cortex with redundant information various sensory stimuli are gated cortically such that response to stimulus 2 (S2) is significantly reduced in amplitude compared to stimulus 1 (S1). Upper airway protective mechanisms, such as swallowing and cough, are dependent on sensory input for triggering and modifying their motor output. Thus, it was hypothesized that central neural gating would be absent for paired air puff stimuli applied to the oropharynx. Twenty-three healthy adults (18-35 years) served as research participants. Pharyngeal sensory evoked potentials (PSEPs) were measured via 32 electrode cap (10-20 system) connected to SynAmps2 Neuroscan EEG System. Paired-pulse air puffs were delivered with an inter stimulus interval of 500ms to the oropharynx using a thin polyethylene tube connected to a flexible laryngoscope. Data were analyzed using descriptive statistics and a repeated measures analysis of variance. There were no significant differences found for the amplitudes S1 and S2 for any of the 4 component PSEP peaks. Mean gating ratios were above 0.90 for each peak. Results supports our hypothesis that sensory central neural gating would be absent for component PSEP peaks with paired-pulse stimuli delivered to the oropharynx. This may be related to the need for constant sensory monitoring necessary for adequate airway protection associated with swallowing and coughing.